2009
DOI: 10.1590/s1413-86702009000100008
|View full text |Cite
|
Sign up to set email alerts
|

Genotypes and clinical data of respiratory syncytial virus and metapneumovirus in brazilian infants: a new perspective

Abstract: The aim of this study was to determine if there was a correlation between respiratory syncytial virus (RSV) and metapneumovirus (MPV) genotypes and clinical data of Brazilian infants hospitalized for acute lower respiratory infection. The viruses in the patients' nasopharyngeal secretions were studied using the polymerase chain reaction and phylogenetic analysis. The study assessed 144 infants; 31.9% were RSV positive and 5.6% were MPV positive. Statistical analysis was performed using the chi-squared test, Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 36 publications
1
21
1
1
Order By: Relevance
“…Compared to other tested viruses, RSV was significantly more common in this age group [5]. A predominance of RSV and human metapneumovirus (hMPV) was observed in Brazil and in other countries [9]. While the role of respiratory viruses including hMPV and RSV is well established in causing self-limiting upper respiratory tract infections or mild pneumonia, their contribution to causing severe and radiologically proven pneumonia in developing countries is less clear [10].…”
Section: Introductionmentioning
confidence: 89%
“…Compared to other tested viruses, RSV was significantly more common in this age group [5]. A predominance of RSV and human metapneumovirus (hMPV) was observed in Brazil and in other countries [9]. While the role of respiratory viruses including hMPV and RSV is well established in causing self-limiting upper respiratory tract infections or mild pneumonia, their contribution to causing severe and radiologically proven pneumonia in developing countries is less clear [10].…”
Section: Introductionmentioning
confidence: 89%
“…Several G protein genotypes within the two subtypes have been identified, including GB1 to GB4 (24). SAA1, SAB1, SAB2, and SAB3 were identified in South Africa (39) and, subsequently, in various other geographic locations (26,30). Venter et al (38) also showed that identical RSV genotypes were identified in different regions in South Africa during one season.…”
Section: Respiratory Syncytial Virus (Rsv) a Member Of The Genusmentioning
confidence: 99%
“…Brazil has already been demonstrated 3,5,8,31,35 . No vaccine or antiviral therapy is currently available for prevention or treatment of HMPV infection.…”
Section: The Burden Of Hmpv Infection Inmentioning
confidence: 99%